Analisis Keinginan dan Kepuasan Konsumen Terhadap Produk Inovasi Mochi Crackers dengan Menggunakan Pendekatan CSI dan IPA - Arista, Intan; Sindi Rustilawati; Muhammad Hibar Pangestu; Wirasena Rukasah; Dewi Lestari; Khoirul Aziz Husyairi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze consumer desires and satisfaction with Mochi Crackers innovation products using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) approaches. Indonesia's food and beverage sector, especially snacks, continues to grow by creating innovative products such as Mochi Crackers, which adapts the traditional mochi snack into a modern product with a longer shelf life and crunchy texture. A survey was conducted involving 50 respondents from various backgrounds, using a Likert scale to measure the level of satisfaction and importance of product attributes. The results showed that the majority of consumers were attracted to this product because of its practicality, taste, and affordable price. Through the CSI analysis, a satisfaction index was obtained which shows the overall level of consumer satisfaction. Meanwhile, IPA analysis identifies product attributes that need to be improved to improve product quality and competitiveness in the market. This study provides recommendations to Mochi Crackers manufacturers to focus on improving the quality of packaging and promotion to strengthen the product's position in the market.